2015
DOI: 10.1016/j.mbs.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of a nutrient–phytoplankton system with toxic effect on phytoplankton

Abstract: Chattopadhyay, J. (2015). Spatial dynamics of a nutrientphytoplankton system with toxic effect on phytoplankton. Mathematical Biosciences, 264, 94-100. https://doi.org/10.1016Biosciences, 264, 94-100. https://doi.org/10. /j.mbs.2015 Spatial dynamics of a nutrient-phytoplankton system with toxic effect on phytoplankton AbstractThe production of toxins by some species of phytoplankton is known to have several economic, ecological, and human health impacts. However, the role of toxins on the spatial distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…In 1949, Riley et al [38] first used the mathematical model to study the nutrient-plankton dynamics, which leads to the formulation of a growing number of mathematical models to describe the nutrient-phytoplankton dynamics or nutrient-plankton dynamics, and many dynamic mechanisms of phytoplankton growth response to various factors have been revealed [14,15,22,[39][40][41][42][43][44][45][46][47]. For example, Chen et al [43] showed that the proper control of the ratio for nitrogen and phosphorus can more effectively control and eliminateblue-green algae blooms.…”
Section: Introductionmentioning
confidence: 99%
“…In 1949, Riley et al [38] first used the mathematical model to study the nutrient-plankton dynamics, which leads to the formulation of a growing number of mathematical models to describe the nutrient-phytoplankton dynamics or nutrient-plankton dynamics, and many dynamic mechanisms of phytoplankton growth response to various factors have been revealed [14,15,22,[39][40][41][42][43][44][45][46][47]. For example, Chen et al [43] showed that the proper control of the ratio for nitrogen and phosphorus can more effectively control and eliminateblue-green algae blooms.…”
Section: Introductionmentioning
confidence: 99%
“…However, nutrients play a big role in the growth of plankton. As far as we know, the nutrient-plankton systems have been considered by a number of scholars [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of nutrients can better explain their mechanism in the phytoplankton-zooplankton system. As far as we know, the nutrient-plankton systems have been considered by a number of scholars [14][15][16][17][18][19][20][21]. Chakrabortyour et al [14] demonstrated that the toxin producing phytoplankton (TPP) species control the bloom of other nontoxic phytoplankton species when nutrient-deficient conditions are favorable for TPP species to release toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [16] proposed a nutrient model for a water ecosystem. Chakraborty et al [17] investigated spatial dynamics of a nutrient-phytoplankton system with toxic effect on phytoplankton. Wang et al [18] analyzed a nutrient-plankton model with delayed nutrient cycling.…”
Section: Introductionmentioning
confidence: 99%